2016
DOI: 10.1002/ijc.30470
|View full text |Cite
|
Sign up to set email alerts
|

High cardiovascular disease mortality after endometrial cancer diagnosis: Results from the Surveillance, Epidemiology, and End Results (SEER) Database

Abstract: Obesity is a strong risk factor for developing endometrial cancer and cardiovascular disease (CVD); consequently, understanding CVD mortality among endometrial cancer survivors is important. We analyzed Surveillance, Epidemiology and End Results Program data for 157,496 endometrial cancer cases diagnosed between 1988 and 2012. We calculated standardized mortality ratios (SMRs) for CVD and all-cause mortality comparing endometrial cancer cases and general population women. We categorized women into one of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 44 publications
6
63
0
Order By: Relevance
“…We found a significantly higher risk of CVM among patients with NHL than in the general US population and in patients with other cancers known to be associated with increased CVM risk. A SEER‐based study reported SMRs of 1.61 (95% CI: 1.21‐2.24) in patients with testicular seminoma, 2.4 (95% CI: 2.1‐2.7) in those with oral and oropharyngeal squamous carcinoma, and 8.8 (95% CI: 8.7‐9) in those with endometrial cancer . Furthermore, the higher risk was more pronounced among younger patients, as the SMR for CVM decreased with age.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significantly higher risk of CVM among patients with NHL than in the general US population and in patients with other cancers known to be associated with increased CVM risk. A SEER‐based study reported SMRs of 1.61 (95% CI: 1.21‐2.24) in patients with testicular seminoma, 2.4 (95% CI: 2.1‐2.7) in those with oral and oropharyngeal squamous carcinoma, and 8.8 (95% CI: 8.7‐9) in those with endometrial cancer . Furthermore, the higher risk was more pronounced among younger patients, as the SMR for CVM decreased with age.…”
Section: Discussionmentioning
confidence: 99%
“…The association between CVD risk after an EC diagnosis has been examined in a retrospective analysis of the Surveillance, Epidemiology, End Results (SEER) program [10] and in two cohort studies including EC cases and matched, cancer-free women [11, 12]. In our SEER analysis, we demonstrated an eight-fold higher risk of CVD mortality among 157,496 women with EC compared with women in the general population [10].…”
Section: Discussionmentioning
confidence: 83%
“…In our SEER analysis, we demonstrated an eight-fold higher risk of CVD mortality among 157,496 women with EC compared with women in the general population [10]. The major limitations of the SEER analysis included the use of an external comparison group that may have differed in key ways from the cancer cases and the inability to adjust for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential solution to this would be to apply multivariate modeling procedures as in the Fine-Gray model (Fine & Gray, 1999) as used by Felix et. al (Felix et al, 2017). However, that approach is only applicable for a proportional hazards model.…”
Section: Discussionmentioning
confidence: 99%